ARAGON REYES, Manuel (Dir.); GAHETE JURADO, Manuel y BENLABBAH, Fatiha (Eds.). El Protectorado español en Marruecos. La historia trascendida. Bilbao: Iberdrola, 2013 (Mohammed Dahiri) - DAHIRI, Mohammed (Al-Andalus Magreb, 2014)
Es una reseña.